2019
DOI: 10.3390/molecules24050870
|View full text |Cite
|
Sign up to set email alerts
|

Study on Antidepressant Activity of Pseudo-Ginsenoside HQ on Depression-Like Behavior in Mice

Abstract: Suppressive effects of ginsenoside Rh2 (Rh2), (24R)-pseudo-ginsenoside HQ (R-PHQ), and (24S)-pseudo-ginsenoside HQ (S-PHQ) against lipopolysaccharide (LPS)-induced depression-like behavior were evaluated using the forced swimming test (FST) and tail suspension test (TST) in mice. Pretreatment with Rh2, R-PHQ, and S-PHQ significantly decreased immobility time in FST and TST with clear dose-dependence, and significantly downregulated levels of serum tumor necrosis factor-α and interleukin-6, and upregulated supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…After screening with the set standards of OB ≥30% and DL ≥0.18, 33 potentially active ingredients were retrieved from TCMSP and TCMID, among which 7 were potential active ingredients of Hyacinth chrysoides, 11 were potential active ingredients of Panax quinquefolium, 4 were potential active ingredients of Acorus tatarinowii, and 15 were potential active ingredients of turmeric. Ginsenoside rh2 and its metabolites can reduce the activity duration of forced swimming test (FST) and tail suspension test (TST) in mice and improve the depression-like behavior induced by lipopolysaccharide (LPS), showing the highest antidepressant effect at 30 mg/kg [ 42 ]. Kaempferol alleviated hippocampal neuron injury in CUMS depression model rats by inhibiting autophagy and oxidative stress [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…After screening with the set standards of OB ≥30% and DL ≥0.18, 33 potentially active ingredients were retrieved from TCMSP and TCMID, among which 7 were potential active ingredients of Hyacinth chrysoides, 11 were potential active ingredients of Panax quinquefolium, 4 were potential active ingredients of Acorus tatarinowii, and 15 were potential active ingredients of turmeric. Ginsenoside rh2 and its metabolites can reduce the activity duration of forced swimming test (FST) and tail suspension test (TST) in mice and improve the depression-like behavior induced by lipopolysaccharide (LPS), showing the highest antidepressant effect at 30 mg/kg [ 42 ]. Kaempferol alleviated hippocampal neuron injury in CUMS depression model rats by inhibiting autophagy and oxidative stress [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, SIRT1 overexpression has shown significant neuroprotective effects, increasing the level of BDNF [158]. Also, Shen et al (2019) [159] and Chen et al (2019) [160] showed that BDNF and SIRT1-related pathway activation produced strong effects, similar to those obtained with classic antidepressants. According to various studies showing the ability of PPARγ agonists to induce the expression of BDNF [124], it is possible to propose a possible effect of drugs, such as RSG, in improving cognitive symptoms typical of schizophrenia.…”
Section: Pparγ In Schizophreniamentioning
confidence: 93%
“…FST has been modified according to the documentary method [ 12 ]. In short, 1 h after administration, mice were placed in a Perspex bucket (height 25 cm, diameter 12 cm), filled with water to a height of 10 cm (water temperature was kept at 23 ± 2°C).…”
Section: Methodsmentioning
confidence: 99%